2022
DOI: 10.1007/s00203-022-03114-2
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and antimicrobial-resistance of shiga toxin-producing E. coli (STEC) Isolated from edible shellfish and its public health significance

Abstract: Shiga toxin-producing E. coli (STEC) are an important cause of foodborne illness in humans with infections ranging from mild non-bloody diarrhea to bloody diarrhea (BD) and hemolytic uremic syndrome (HUS). This study aimed to investigate the distribution of STEC in shellfish from coastal shores of Lake Timsah in Ismailia Governorate, Egypt and its probable hazard to seafood consumers. Samples from the external surface and tissues of shrimp (n = 45), crabs (n = 45), and oysters (n = 45) batches were examined ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…CC25 exhibits less pronounced seasonality and, again, this may reflect bespoke source and/or transmission routes specific to this type. Other studies have reported an association between isolates belonging to CC25 and prevalence in the ovine reservoir, whereas CC442 has a wider host range [29, 43–46, 48–51, 55]. However, even if this association was confirmed, it is unclear how this might impact on seasonality patterns.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…CC25 exhibits less pronounced seasonality and, again, this may reflect bespoke source and/or transmission routes specific to this type. Other studies have reported an association between isolates belonging to CC25 and prevalence in the ovine reservoir, whereas CC442 has a wider host range [29, 43–46, 48–51, 55]. However, even if this association was confirmed, it is unclear how this might impact on seasonality patterns.…”
Section: Discussionmentioning
confidence: 96%
“…Travel abroad was during the pandemic but based on available data the proportion of cases reporting travel were similar for CC33 and CC442. Previous studies have shown that CC442 may be associated with colonisation of a broad range of animal hosts and may be ubiquitous in the environment [29,[43][44][45][46]55]. Survival in the environment and persistence in the animal reservoir and the food chain have been linked to the presence of genes conferring resistance to tellurite [56,57].…”
Section: Discussionmentioning
confidence: 99%
“…STEC poses health risks to animal reservoirs and food products with respect to easy transmission, causing outbreaks, and transferring resistance genes to Qabili et al 2022;Carter et al 2023;El-Bastawisy et al 2023). Therefore, prevention of STEC infection must be strengthened to avoid the spread of STEC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Enterobacteriaceae regroups important seafood-borne pathogens, and include genera like Escherichia [ 23 , 24 ], Shigella which was reported in Japan [ 25 ], Salmonella [ 26 , 27 , 28 , 29 , 30 , 31 ] and Klebsiella in Portugal [ 32 ], Tunisia [ 33 ] and Italy [ 34 ], which have drawn attention to their health threats and their contribution to the spread of antibiotic resistance in the environment ( Figure 1 and Supplementary Table S1 ).…”
Section: Shellfish May Be Contaminated By a Large Diversity Of Pathogensmentioning
confidence: 99%